2015
DOI: 10.1007/s00264-015-2929-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic potential of in vitro osteo-induced adipose-derived mesenchymal stem cells combined with platelet-rich plasma in an ectopic model

Abstract: The combination of in vitro osteo-induced ADSCs and PRP on BMM carrier represents a promising approach for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The results of these studies, bolstered by the results of in vitro and animal studies, indicate that bone marrow derived MSCs carry little to no risk of malignant transformation, and that they are likely safe for use in human orthopaedic applications [4,7,[13][14][15]. However, no large scale investigations exist with long-term patient follow-up where all complications have been reported, adjudicated, and classified.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of these studies, bolstered by the results of in vitro and animal studies, indicate that bone marrow derived MSCs carry little to no risk of malignant transformation, and that they are likely safe for use in human orthopaedic applications [4,7,[13][14][15]. However, no large scale investigations exist with long-term patient follow-up where all complications have been reported, adjudicated, and classified.…”
Section: Introductionmentioning
confidence: 93%
“…Because MSCs can differentiate into bone, cartilage, muscle, tendon, and ligament tissue and can use paracrine and other effects to elicit significant changes in injured tissues, their use for treating orthopaedic conditions holds significant promise [2][3][4][5]. In a clinical setting MSCs are typically harvested from bone marrow, then isolated and either re-injected or implanted in the same surgical procedure or culture expanded and then used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a question regarding interactions between cells of fat origin and the CaP coating has arisen despite the poor (1 of 9 cases) EO features of hAMSCs not treated with recombinant BMP2 and subcutaneously implanted in immunodeficient mice on porous CaP ceramic particles [ 54 ]. At 8 weeks, weak vascularization and EO induced by mouse AMSCs immobilized on bone substitute material Bio-Oss were reported [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, materials based on hydroxyapatite and β-tricalcium phosphate are suitable for BTE [42]. In addition, materials based on bone mineral matrix are frequently used [43][44][45][46]. Also, regulatory factors are not less important components in BTE, and at the first place, they should induce and support osteogenic differentiation, adhesion, and proliferation of implanted cells.…”
Section: Bone Substitutes and Regulatory Factorsmentioning
confidence: 99%
“…Finally, there is a growing interest about synergistic effects of ADSCs and PRP for bone regeneration. Many studies reported promising osteogenic potential of ADSCs and PRP combination [46,55,56,59] and stimulative potential of PRP that improves osteogenesis in combination with cells [51,60]. In addition, Fernandes and Yang [49] reviewed and summarized some recently published data which implies that adipose-derived stem cells obtained from human, mouse, rat and rabbit in combination with PRP in in vitro and/or in vivo conditions are related with outcomes which are of benefit for BTE [49].…”
Section: Bone Substitutes and Regulatory Factorsmentioning
confidence: 99%